Auditoría de Gestión a la Cooperativa de Ahorro y Crédito Sumak Kawsay Ltda., Agencia La Maná provincia de Cotopaxi, período 2018. - Cunuhay Pilatasig, Mercy Yolanda (2020)
The Management Audit is important because it constitutes a means through which organizations seek continuous improvement for its operation, enabling the identification of areas that present difficulties, related causes and solutions to improve, locate opportunities to eliminate waste and inefficiencies. ; Therefore, this research had as a general objective, to carry out a Management Audit of the Sumak Kawsay Ltda. Savings and Credit Cooperative La Maná Agency, Cotopaxi Province, 2018 period, to measure the level of effectiveness, efficiency and economy in use of your resources For the fulfillment of the stated objectives, basic research was used, because through it the academic knowledge of the authors was increased, so also the bibliographic research was used to gather theoretical information on the main variables that incur in the development of a Management Audit. The field investigation for the application of the techniques of the interview to the Head of Agency, employee surveys and the internal control questionnaire to the components of Governance, Operational, Credit, Funding and Accounting. The methods applied were quantitative, deductive and inductive. The universe population was made up of 1 Head of Agency and 8 employees working in the financial institution. The application of the interview allowed to know that the executives of the Cooperative have not yet noticed the importance of the application of audits, since an audit program that establishes the frequency of its performance has not been determined. Through the evaluation of internal control, a confidence level of 78% and a risk of 22% could be evidenced. The management indicators allowed to establish flaws regarding the dissemination of the strategic plan, there was a significant growth in the number of partners and the decrease in the delinquency rate stood at 1.16%. The findings detected were: absence of risk analysis for the administrative area, no indicators of efficiency and effectiveness have been defined, lack of a customer service protocol, the windows of the cooperative do not have bulletproof glass, inadequate control over the origin of the money collected, inefficiency in reconciliations of the major auxiliary balance with the financial statements with their respective conclusions and recommendations.